Flavonoid and Alkaloid Content of Red Onion Skin Extract (Allium cepa L.) - Windarsih, Yulia; Masrianih; Trianto, Manap (Jurnal Biologi Tropis, 2025)
Red onion skin (Allium cepa L.) is often discarded as waste, despite being rich in flavonoids and alkaloids, which possess antioxidant, anti-inflammatory, antimicrobial, and anticancer properties. This study aims to determine the flavonoid and alkaloid content of red onion skin extract using reflux and Soxhlet extraction methods with 96% ethanol as the solvent. The extraction was performed using reflux and Soxhlet techniques, followed by UV-Vis spectrophotometry to quantify flavonoid and alkaloid content. A quercetin standard curve was used to determine flavonoid levels, while a caffeine standard curve was applied for alkaloid content analysis. The Soxhlet method yielded a higher flavonoid content (108.21 mg/g or 10.82%) compared to the reflux method (105.55 mg/g or 10.55%). In contrast, the reflux method resulted in a higher alkaloid content (169.56 mg/g or 16.95%) than Soxhlet extraction (167.0 mg/g or 16.70%). These differences are attributed to the continuous solvent circulation in Soxhlet extraction, which enhances flavonoid solubility, while the lower temperature in the reflux method prevents alkaloid degradation. The findings suggest that Soxhlet extraction is more effective for flavonoid extraction, whereas reflux extraction is better for alkaloid extraction. Given their significant bioactive properties, red onion skin extracts have potential applications in the pharmaceutical, nutraceutical, and food industries. Future research should focus on optimizing extraction techniques and conducting toxicological and pharmacological studies to explore the therapeutic potential of red onion skin extract.